Pathogenetic and Combined Treatment of Iron Deficiency Anemia with Drugs Increasing Erythropoiesis - Gulshanoi Akmaljonovna Karimkulova; Yuldasheva Nodira Ergashevna (Genius Journals, 2023)
An increase in the amount of iron in the body leads to stimulation of the synthesis of hepcidin, which reduces iron absorption in the intestine, transport and circulation. In turn, a decrease in iron absorption in the intestine leads to inhibition of hepcidin synthesis in the liver and, in feedback, to the restoration of iron uptake from food and intestines. So far, antibodies against hepcidin have not been obtained and it is not possible to measure its level in a clinical setting. Work in this direction is underway.
Keywords: hepcidin; iron amounts; transport protein